Metabolismo de la vitamina D y su papel en la enfermedad de Alzheimer - Avila U., Fernanda; Arévalo, Nohela B.; SanMartin, Carol D (Revista Hospital Clínico Universidad de Chile, 2024)
Alzheimer disease (AD) is a type of dementia that affects memory, thinking and behavior. Meanwhile, mild cognitive impairment (MCI) is the transitional period between normal aging and dementia, and is the best predictor of future dementia, with an accelerated rate of progression to AD. Amyloid β peptide (Aβ) deposition in AD is due to an imbalance in the production/clearance rate. Vitamin D is a multipurpose secosteroid hormone classically associated with calcium homeostasis, bone formation, and maintenance. However, currently know that vitamin D is a neurosteroid affecting brain development and function; implications for neurological and psychiatric disorders. Many studies have linked low plasma levels of vitamin D with a high prevalence of MCI and AD. Vitamin D acts through its specific nuclear receptor (VDR), which is a transcription factor that binds to the Vitamin D Response Element in the genome. Aβ peptide is transported across the blood brain barrier by LRP1 and P-gp as efflux transporters and RAGE as influx transporter. Numerous evidence indicates that vitamin D modulates the clearance of the Aβ peptide through the regulation of LRP1 and P-gp transporters. This evidence supports the importance of vitamin D food fortification policies recently approved in Chile.